(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2012)
The Nordic Noir has been applied by many countries as a slightly distorting mirror of tendencies in their own societies. On the background of its international appeal, the article analyses the prevalent genre of The Killing political drama and melodrama. The elements of the noir design in the introductory sequences – their common traits and the differences that match prevalent plots in each season – are highlighted. The developments taking place in the dominant points of view are traced, from the combination between the local politics and the domestic levels in the first season of the series, to the focus on foreign politics with domestic dimensions in the second season, and the reversion to domestic politics, this time combined to a global dimension, in the last season. Similarities and differences in the plots, and their relationship to (and interpretation of) events and phenomena in the modern Danish welfare state and in the Western sphere, are also investigated.